What technologically proficient communities want from V2X: transport–environment implications from online discussions - Ondrej Havran; David Watling; Haibo Chen; Wen-Long Shang; Ye Liu; Chenxi Wang; Zhao Wang; Dingsong Cui; Dongyao Jia (Travel Behaviour and Society, 2026)

Empirical evaluation of battery swapping technology adoption in urban electric taxi operations - Dingsong Cui; Haibo Chen; David Watling; Ye Liu; Wen-Long Shang; Chenxi Wang; Peng Liu; Chengcheng Xu; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2026)

Impact of low-emission driving behavior on brake wear PM emissions: insights from a real-world evaluation - Ye Liu; Tangjian Wei; Haibo Chen; Sijin Wu; Yili (Kelly) Tang; Zhiyuan Lin; David Watling; Jingwen Yao; Nansong Yue; Chenxi Wang; Dingsong Cui; Dimitris Margaritis (Transportation Research Part D: Transport and Environment, 2025)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Efficacy of Multimodal Sensory Therapy in Adult Acquired Brain Injury: A Systematic Review - Michael Francis Norwood; Ali Lakhani; David Phillip Watling; Chelsea Hannah Marsh; Heidi Zeeman (Neuropsychology Review, 2023)
Adults who experience an acquired brain injury often experience disorders of consciousness, physical difficulties, and maladaptive behaviours. Multimodal sensory therapy may benefit brain injured patients, however the extent this therapy can facilitate rehabilitation is not well understood. This systematic review aimed to synthesize multimodal sensory therapy research for adults affected by acquired brain injury. PRISMA guidelines were followed and searches for work published up until July 2021 were undertaken in 5 databases, finding 1054 articles. 43 articles were included in the study. Results describe 29 studies related to coma following an acquired brain injury and 14 to no coma studies (mostly stroke). Multimodal sensory therapy was mostly used as a coma arousal technique following traumatic brain injury, finding positive effects. Multimodal sensory therapy was less applied in stroke, no coma rehabilitation, where most studies found improvement in somatosensory sensation and motor control in an affected limb. In several no coma studies, effects were maintained after several months. The most common senses stimulated in coma studies were audio ( N = 30), tactile ( N = 28), visual ( N = 26), olfactory ( N = 22), and gustatory ( N = 17), while the most common senses stimulated in stroke, no coma studies were proprioception ( N = 7), tactile ( N = 8), and stereognosis ( N = 4). Multimodal sensory therapy can be beneficial for patients, especially those in a minimally conscious state or attempting physical rehabilitation following stroke. Negative findings are infrequent in the current literature base. Multimodal sensory therapy appears to be a low-risk intervention with positive outcomes.

Clinical Bridging Studies and Modeling Approach for Implementation of a Patient Centric Sampling Technique in Padsevonil Clinical Development - Hester Kramer; Ceyhun Bicer; Christian Otoul; Chiara Rospo; Merran Macpherson; Mark Watling; Massimo Bani; David Sciberras; Hugues Chanteux (The AAPS Journal, 2023)
Volumetric absorptive microsampling (VAMS) techniques have gained popularity these last years as innovative tool for collection of blood pharmacokinetic (PK) samples in clinical trials as they offer many advantages over dried blood spot and conventional venous blood sampling. The use of Mitra ® , a blood collection device based on volumetric absorptive microsampling (VAMS) technology, was implemented during clinical development of padsevonil (PSL), an anti-seizure medication (ASM) candidate. The present study describes the approach used to bridge plasma (obtained from conventional venous blood sampling) and blood exposures (obtained with Mitra ® ) to support the use of Mitra as sole blood PK sampling method in clinical trials. Paired blood (using Mitra ® ) and plasma samples (using conventional venous blood sampling) were collected in healthy volunteers as well as in patients with epilepsy. PSL concentration in plasma and blood were analyzed using different approaches which included evaluation of blood-to-plasma ratios (B/P) over time, linear regression, Bland-Altman analysis as well as development of a linear-mixed effect model based on clinical pharmacology studies. Results showed that the observed in vivo B/P and the measured bias between the 2 collection methods were consistent with the measured in vitro B/P. Graphical analysis demonstrated a clear time effect on the B/P which was confirmed in the linear mixed effect model with sampling time identified as significant covariate. Finally, the built-in model was validated using independent datasets and was shown to adequately predict plasma concentration based on blood concentration with a mean bias of less than 9% (predicted versus observed plasma concentration). Graphical Abstract

Using smart card data to model public transport user profiles in light of the COVID-19 pandemic - Maximiliano Lizana; Charisma Choudhury; David Watling (Travel Behaviour and Society, 2023)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Thermal biology mediates responses of amphibians and reptiles to habitat modification - A. Justin Nowakowski; James I. Watling; Michelle E. Thompson; George A. Brusch; Alessandro Catenazzi; Steven M. Whitfield; David J. Kurz; Ángela Suárez‐Mayorga; Andrés Aponte‐Gutiérrez; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2018)
Human activities often replace native forests with warmer, modified habitats that represent novel thermal environments for biodiversity. Reducing biodiversity loss hinges upon identifying which species are most sensitive to the environmental conditions that result from habitat modification. Drawing on case studies and a meta‐analysis, we examined whether observed and modelled thermal traits, including heat tolerances, variation in body temperatures, and evaporative water loss, explained variation in sensitivity of ectotherms to habitat modification. Low heat tolerances of lizards and amphibians and high evaporative water loss of amphibians were associated with increased sensitivity to habitat modification, often explaining more variation than non‐thermal traits. Heat tolerances alone explained 24–66% (mean = 38%) of the variation in species responses, and these trends were largely consistent across geographic locations and spatial scales. As habitat modification alters local microclimates, the thermal biology of species will likely play a key role in the reassembly of terrestrial communities.

Tropical amphibians in shifting thermal landscapes under land‐use and climate change - A. Justin Nowakowski; James I. Watling; Steven M. Whitfield; Brian D. Todd; David J. Kurz; Maureen A. Donnelly (Conservation Biology, 2017)
Land‐cover and climate change are both expected to alter species distributions and contribute to future biodiversity loss. However, the combined effects of land‐cover and climate change on assemblages, especially at the landscape scale, remain understudied. Lowland tropical amphibians may be particularly susceptible to changes in land cover and climate warming because many species have narrow thermal safety margins resulting from air and body temperatures that are close to their critical thermal maxima (CT max ). We examined how changing thermal landscapes may alter the area of thermally suitable habitat (TSH) for tropical amphibians. We measured microclimates in 6 land‐cover types and CT max of 16 frog species in lowland northeastern Costa Rica. We used a biophysical model to estimate core body temperatures of frogs exposed to habitat‐specific microclimates while accounting for evaporative cooling and behavior. Thermally suitable habitat area was estimated as the portion of the landscape where species CT max exceeded their habitat‐specific maximum body temperatures. We projected changes in TSH area 80 years into the future as a function of land‐cover change only, climate change only, and combinations of land‐cover and climate‐change scenarios representing low and moderate rates of change. Projected decreases in TSH area ranged from 16% under low emissions and reduced forest loss to 30% under moderate emissions and business‐as‐usual land‐cover change. Under a moderate emissions scenario (A1B), climate change alone contributed to 1.7‐ to 4.5‐fold greater losses in TSH area than land‐cover change only, suggesting that future decreases in TSH from climate change may outpace structural habitat loss. Forest‐restricted species had lower mean CT max than species that occurred in altered habitats, indicating that thermal tolerances will likely shape assemblages in changing thermal landscapes. In the face of ongoing land‐cover and climate change, it will be critical to consider changing thermal landscapes in strategies to conserve ectotherm species.

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

Climate downscaling effects on predictive ecological models: a case study for threatened and endangered vertebrates in the southeastern United States - David N. Bucklin; James I. Watling; Carolina Speroterra; Laura A. Brandt; Frank J. Mazzotti; Stephanie S. Romañach (Regional Environmental Change, 2013)

Global diversity and distribution of macrofungi - Gregory M. Mueller; John P. Schmit; Patrick R. Leacock; Bart Buyck; Joaquín Cifuentes; Dennis E. Desjardin; Roy E. Halling; Kurt Hjortstam; Teresa Iturriaga; Karl-Henrik Larsson; D. Jean Lodge; Tom W. May; et al. (Biodiversity and Conservation, 2007)

Fungal biodiversity: a British Mycological Society Symposium - Roy Watling; David L. Hawksworth (Biodiversity and Conservation, 1997)

Environmental control of metabolic fluxes in thermotolerant methylotrophic Bacillus strains - Anthony G. Brooke; Elizabeth M. Watling; Margaret M. Attwood; David W. Tempest (Archives of Microbiology, 1989)